AN APPRAISAL OF THE REVISED NIGERIA CERTIFICATE IN EDUCATION MINIMUM STANDARDS (ENGLISH LANGUAGE CURRICULUM) - Oritsebemigho, Tom-Lawyer Oris (European Scientific Journal, ESJ, 2014)
This paper gives a concise appraisalof the revised Nigeria Certificate in Education Minimum Standards (English Language Curriculum). The certificate is the basic qualification for teaching. It is a sub-degree (certificate course) and professional teacher diploma, which is obtained after 3 years (full time) at a college of Education (Lassa, 2000). The recent review of the Minimum Standards (Curriculum) of colleges of education by the National Commission for Colleges of Education will be described as a bold stride since curriculum in Nigeria has been viewed as irrelevant to the needs of the students (Okebukola, 2013;Uma, Obidike&Ogwuru , 2013)).Teacher education in the country is in a deplorable state and ‘the teacher training programmes have been indicted’ (Ajelayemi, 2002, cited in Ajelayemi, 2005, para. 5).The review has engendered this appraisal as the penultimate edition of the curriculum was trailed by widespread criticisms. The paper intends to demonstrate the fact that the implementation of the English Language curriculum may suffer setbacks, if some strategies are not established as the quality of college entrants (Akinbote, 2007), the overcrowded classrooms, the non- provision of technological facilities (Adedeji, 2011) and the poor state of libraries in colleges of education (Mohammed, 2012) are pivotal issues that require proactive solutions. It recommends a review of the admission policy, decongestion of classrooms, procurement of current publications in libraries and INSET training of lecturers on the new Minimum Standards for a successful implementation of the curriculum.